Uji Efek Antihiperglikemik Seduhan Daun Sirih Cina (Peperomia Pellicida) Diberikan Secara Oral Pada Mencit Jantan (Mus Musculus) - Ruri Ayu Agrace; Riana Versita; Muhamad Arifin; Dwi Kurnia Putri; Dwi Dominica; Dian Handayani; Ikhsan Ikhsan (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Chinese Betel Plant (Paperomia pellucida) is an herbal plant that has benefits for treating diseases such as acne, ulcers, antidiabetic, antioxidant, anti-inflammatory, antimicrobial, and antibacterial. The content of bioactive compounds from Chinese betel include alkaloids, flavonoids, steroids, saponins, tannins, triterpenoids, and carbohydrates. The aim The purpose of this study was to determine the effect of steeping Chinese betel and on reducing blood glucose levels in male mice. This method used is an experimental method at the Pharmacology Laboratory D3 Pharmacy FMIPA Bengkulu University. The test animals used were three groups, namely the positive control treatment group that received glibenclamide, the negative control treatment group received aquadest, and the 2% Chinese betel steeping treatment group. The results showed that Chinese betel curd was reduced from 125 mg/dl to 93 mg/dl and there was no hypoglycemic decrease in blood glucose due to glibenclamide. From the results of the study it can be concluded that the administration of Chinese betel and glibenclamide steeping is effective in lowering blood glucose levels in male mice.